Breaking Open ‘Civil Society’: Sukumbasi and the City - Ninglekhu, Sabin (New Angle: Nepal Journal of Social Science and Public Policy, 2012)
This article is an ethnographic account of strategies mobilised by sukumbasi (squatter communities) in Kathmandu to meet basic needs such as water and electricity and for claiming landownership rights and citizenship. Particular attention is paid to their organizing practices, the building of solidarity and establishing of linkages which, the author finds, are not dissimilar to those of ‘mainstream’ civil society groups. This observation, in turn, allow the author to highlight the conceptual binaries (such as formal-informal, professionalunprofessional, with the first element of the pair associated with civil society) serving to define ‘civil society’ in Nepal and their exclusionary character. It is suggested that the concept of civil society be broadened so as to include groups, such as the sukumbasi, which do not currently fit neatly into civil society definitions in Nepal.